Slovenska pisma rudarskega nadzornika Lukasa Polca Sigismondu (Žigu) Zoisu v letih od 1789 do 1798 - Schmidt, Goran (Scopolia, 2015)
The treatise deals with Slovenian letters written by the mining supervisor Lukas Polc in the 1789-1798 period to the ironworks owner, merchant, mentor, patron and enlightener Sigismund (Žiga) Zois about mine pits at Gorjuše at the foot of Pokljuka Plateau, a research mine along the Drava River in the Koroška region and clay digging at Selca near Škofja Loka. In his last letter, he expresses his personal gratitude to Zois. The letters are of special relevance as they imply the very first commercial use of Slovenian language ever.
Keywords: ceramic; history; keramika; pisma; Polc, Lukas; rudniki; Slovene; slovenščina; zgodovina; Zois, Žiga, 1747-1819